International engagement in failed states: Choices and trade-offs - Louise Andersen (Danish Institute for International Studies (DIIS), 2005)
Failed states have made it to the top of the international agenda following 11 September 2001. This paper gives an overview of the debate on `what to do'. Firstly, it suggests an explanation of where these so-called failed states are coming from: Why do some states self-destruct? Secondly, four different approaches to failed states are presented and discussed - with special emphasis on the dilemmas and predicaments they each hold. The paper concludes that the question of what to do with failed states requires a political answer. Not a technical one. – – Fejlslagne stater er - ikke mindst efter 11. september 2001 - kommet højt på den internationale dagsorden. I dette papir gives et overblik over diskussionen om, hvad det internationale samfund skal og kan gøre. Indledningsvist gives en mulig forklaring på, hvor disse såkaldte `fejlslagne' stater kommer fra: Hvorfor - og hvordan - er der nogle stater, der tilsyneladende selvdestruerer? Papiret diskuterer derefter fire forskellige forslag til løsninger - med særlig vægt på de dilemmaer de hver især indeholder. Papiret konkluderer, at spørgsmålet om hvad man skal stille op med verdens fejlslagne stater først og fremmest handler om politik - ikke om teknik.
Keywords: 330